URGENSI DAN KENDALA PENERAPAN ASAS CABOTAGE DALAM PELAYARAN DOMESTIK INDONESIA DI ERA PERDAGANGAN BEBAS - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2007)
This objectives of this paper are to study the urgency of the application of the cabotage principle for domestic shipping and to find out obstacles for its implementation faced by Indonesia as a maritime country, This principle determines that a country has a right to prohibit foreign vessels to conduct commercial matter using its seashore of its territorial water. The result of this analysis suggests that Indonesia has not consistenir implemented the cabotage principle in domestic shipping For the domestic transport of goods, Indonesian ships can only be able to carry out 56,4 percent, while foreign ships carry uut the rest. Another problem is that the cabotage principle has not been fully supported by appropriate laws, government policy banking and investment. Therefore, Indonesia shipping is left behind. Kaki kunci : Cabotage, Pelcrvaran Dornestik, Perdagangan Rebus